Is There Any Effect of the Chronobiological Profile on Auditory Skills? - Didem Şahin Ceylan; Gökçe Gültekin; Yeter Saçlı; Busemnaz Avşar Aksu; Büşra Aksu (Türk Uyku Tıbbı Dergisi)
Objective: This study aimed to investigate the peripheral and central auditory performance of circadian chronotypes at different times of the day. Materials and Methods: The participants, whose chronotypes were determined using the morningness eveningness questionnaire, underwent acoustic immittance measurements, Otoacoustic Emission test, Pure Tone Audiometry test, Frequency Pattern test, Duration Pattern test (DPT), Turkish speech in noise (TSiNT) and Auditory Verbal Learning test (AVLT) both in the morning and evening. A total of 63 participants with normal hearing and montreal cognitive assessment score ≥21 were included. Results: Morning types scored significantly higher on the A7 subtest of the AVLT during the morning session (p<0.05). Evening types achieved significantly higher scores on the TSiNT during the evening session (p<0.05). In the morning tests, morning types showed significantly better performance on the left ear DPT compared to intermediate types (p<0.05). Similarly, in the evening tests, morning types outperformed intermediate types on the TSiNT (p<0.05). Conclusion: The results indicated that the central auditory performance of individuals with the same chronotype varies at different times of the day, influenced by their circadian profile.